Assessing the Contribution of Vision 2020 Umurenge Programme on Poverty Reduction in Kigabiro Sector, Rwanda (International Journal of Scientific Research and Management (IJSRM), 2021)
The study aimed at assessing the contribution of VUP in poverty reduction especially in Kigabiro sector. This study has general objective which is to assess the contribution of Vision 2020 Umurenge programme on poverty reduction supported by three specific objectives which are to assess the contribution of public works on poverty reduction, to determine the contribution of financial services on poverty reduction, and also to evaluate the contribution of direct support services on poverty reduction especially in Kigabiro sector located in Rwamagana district, Eastern province. Internationally, poverty can describe different things in different part of the world to different people, but it can be defined as when people are not able to afford basic needs. USA has come a long way in addressing the problem, but progress seems to have slowed despite the recent years of economic recovery. In Africa, hundred millions of people in the poorer countries are worries only with survival and elementary needs and average poverty rate for sub-Saharan Africa stands at about 41 percent, and of the world’s 28 poorest countries, 27 are in sub-Saharan Africa all with a poverty rate above 30 percent. Referring to Rwanda, because may people in Rwanda live in rural area, they also live-in poverty line which is so hard for GoR to answer each Rwandan’s problem but poverty alleviation program has been established in order to reduce gap of lower bad living condition of Rwandans due to genocide took place in 1994 against Tutsi. In 1994 the poverty rate was 78%, in year of 2000 poverty rate was 60.4%, 2011 poverty rate was 44.9%. 2014 poverty rate was 39.1% and in 2020 poverty rate was 20%. So, even if the poverty rate mentioned above are decreasing, poverty rate of 20% in 2020 is still high meaning that many people are in the poverty which is the main problem in this studies.